Relación entre composición y densidad de la cubierta vegetal leñosa y las características superficiales del suelo en Bosques Mixtos de Quercus del Sur de la Península Ibérica (Tendencias Actuales de la Ciencia del Suelo, 2004)
We studied the relationships between different estimates of the woody canopy density; different estimates of litter release and accumulation, and different soil properties (mainly soil reaction and macronutrient level) which have been recognised as potentially relevant for plant establishment and development in mixed Quercus forest from Natural Park “do Sudoeste Alentejano e Costa Vicentina”, Portugal (with Q. suber, Q. faginea as dominant tree species) and Natural Park “Los Alcornocales”, Spain (with Q. suber and Q. canariensis). We have found 1) A highly significant, quantitative, relationship between litter accumulation and overall canopy density. These relationships can be established either by using objective (but time-consuming) measures (by sampling or using ad hoc measuring devices) or by calibrated by-eye estimates of three simultaneous observers; 2) A significant relationship between some soil properties (N, P, ammonium) and both canopy density and litter accumulation. We conclude that these relationships are interesting in two ways: 1) They may allow to establish ‘ecotransfer functions’ for these forests (i.e. estimates o predictions about surface litter accumulation or surface values for soil properties, as organic carbon, N or P contents, by using quick field estimates of canopy density or even remote sensing estimates of canopy density), after suitable calibrations. 2) Since some soil chemical properties with known ecological relevance (e.g. C, N, P contents, soil reaction) in forest regeneration may change in a close relationship with other more studied, better known, ecological factors (light, moisture, temperature), attention should be paid to separate direct (e.g. light limitation) versus indirect (soil or litter mediated) effects of woody canopy when evaluating ecological responses at the understorey, while studying forest regeneration processes.